PENGARUH TERPAAN IKLAN 12.12 BIRTHDAY SALE PADA INSTAGRAM @SHOPEE_ID TERHADAP PERILAKU KONSUMTIF (SURVEI PADA FOLLOWERS INSTAGRAM @SHOPEE_ID) - Rafi Bagaskoro Wicaksono Brewijaya Ningrat (2023)
This study aims to explore the influence of exposure to the 12.12 Birthday Sale advertisements presented on the Instagram social media platform on the consumptive behavior of followers of the @shopee_id account. In the digital era, social media has become a crucial platform influencing consumer behavior, particularly in the context of e-commerce shopping. This study will employ a quantitative research method using a survey approach, focusing on descriptive research and utilizing the Advertising Exposure theory to determine the extent of influence of the 12.12 Birthday Sale advertisements on the @shopee_id Instagram account on consumptive behavior. A total of 100 respondents who are followers of the @shopee_id Instagram account are the subjects of this research. Based on the hypothesis testing calculation, the calculated t-value of 6.106 > the tabulated t-value of 1.984, indicating that the alternative hypothesis (H1) is accepted, suggesting a significant and substantial influence of variable X on variable Y. The coefficient of determination indicates a 27.6% level of influence of variable X on variable Y, suggesting a considerable impact on consumptive behavior. Furthermore, the regression coefficient value of 1.192 (positive) indicates a positive impact.